2011
DOI: 10.1016/j.biomaterials.2010.10.052
|View full text |Cite
|
Sign up to set email alerts
|

Tissue integration of growth factor-eluting layer-by-layer polyelectrolyte multilayer coated implants

Abstract: Drug eluting coatings that can direct the host tissue response to implanted medical devices have the potential to ameliorate both the medical and financial burden of complications from implantation. However, because many drugs useful in this arena are biologic in nature, a paucity of delivery strategies for biologics, including growth factors, currently limits the control that can be exerted on the implantation environment. Layer-by-Layer (LbL) polyelectrolyte multilayer films are highly attractive as ultrathi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
226
2
3

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 273 publications
(236 citation statements)
references
References 26 publications
5
226
2
3
Order By: Relevance
“…A primary advantage of the LbL self-assembly technique is the generation of ordered structure at nanometer thickness (with an achievable resolution of 1 nm) on substrates of various shapes and sizes [139]. The drug load can be easily tuned with the number of layers incorporated [140]. The LbL technique has been used to encapsulate drugs onto microsphere substrates [141][142][143].…”
Section: Drug Releasing Microspheres As Cell Carriersmentioning
confidence: 99%
“…A primary advantage of the LbL self-assembly technique is the generation of ordered structure at nanometer thickness (with an achievable resolution of 1 nm) on substrates of various shapes and sizes [139]. The drug load can be easily tuned with the number of layers incorporated [140]. The LbL technique has been used to encapsulate drugs onto microsphere substrates [141][142][143].…”
Section: Drug Releasing Microspheres As Cell Carriersmentioning
confidence: 99%
“…Nowadays these multilayer films are extensively used as reservoirs to host bioactive molecules aiming at biological applications. [6][7][8][9][10] A variety of molecules can be embedded into the films; they include small drugs and dyes, [11][12][13][14][15][16][17] proteins and peptides, [18][19][20][21] or nucleic acids. 22,23 Extensive reviews on the reservoir properties of the multilayers can be found elsewhere.…”
Section: Introductionmentioning
confidence: 99%
“…10,30 The multilayers can release biomolecules reaching the cells thereby inducing cellular response such as adhesion, migration or differentiation. 21,34,35 However, to stimulate a cellular response, it is necessary to ensure the delivery of biomolecules from the film to the cells. To date, stimuli-responsive multilayers have been prepared by employing polymers sensitive to pH, ionic strength, and temperature variation.…”
Section: Introductionmentioning
confidence: 99%
“…The test tube is then immersed in the water bath for temperature control. The drug being released is measured by sampling the releasing medium at sequential time intervals and subjected to drug test using a variety of methods such as standard ELISA [16], radio-labels [17], or UV-Vis absorbance [18]. This static method, though helping to produce a large amount of information on the drug release profiles, does not take into consideration of the physiologically relevant conditions.…”
Section: Introductionmentioning
confidence: 99%